Germination ecology of two troublesome Asteraceae species of rainfed rice: Siam weed (Chromolaena odorata) and coat buttons (Tridax procumbens) - Chauhan, Bhagirath S.; Johnson, David E. (Cambridge University Press, 2008)
Siam weed and coat buttons are among the most troublesome Asteraceae weed species of rainfed rice. The influence of various environmental factors on seed germination and seedling emergence of these weeds was determined. Germination response of both species was greater at the warmer fluctuating temperatures (30/20 and 35/25 C) than at the colder temperatures (25/15 C). Light stimulated germination in both species; however, some seeds still germinated in the dark. Both species were moderately tolerant of salt and water stress, but Siam weed tolerated more stresses than coat buttons. At the soil surface, Siam weed and coat buttons emergence was 75 and 76%, respectively, but this declined rapidly with increasing soil depths. Neither species emerged from depths exceeding 3 cm. Seedling emergence and seedling dry matter of both species were greatly reduced with the addition of crop residue to the soil surface at rates equivalent to 4 to 6 t ha−1. The information gained in this study will be used to facilitate development of effective weed control programs.